Islamic Monitoring as System of Controlling | الرقابة الشرعيىة تطبيقا لنظام الحسبة - Andi Zamakhsyari (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2018)
This research aims to explain the relationship between Raqabah and the concept of Hisbah, and each of them arises from the principle of Promotion of Virtue and Prevention of Vice (al Amru bil al Ma’ruf wa al Nahyu an al Munkar) as a general principle in the Sharia. It is the effectiveness in the Islamic community, whether individuals or society, whether to evaluate the actions and to observe them for the desired purposes, correcting existing mistakes and reconciling between the Islamic rules and the positive laws. The study has shown that Raqabah is one of the implementations of the Hisbah. It is based on Qur’an and Sunnah that revolve around the principle of Promotion of Virtue and Prevention of Vice and Repelling Harms and Procuring Benefits (Dar’u al Mafasid wa Jalb al Masholih).